ANALISA AKUNTABILITAS DAN TRANSPARANSI TENTANG IMPLEMENTASI KEBIJAKAN PENGELOLAAN BOS - Hariswati, Nurul (Journal of Innovation in Business and Economics, 2015)
This  research  was  conducted  with  the  aim  to  analyse  the  implementation  of  the accountability  and  transparency   financial  management  which  the  source  stemming  from government. The approach used is a case study of  indepth interview  from  financial  manager,  head master, and stakeholders. The results of this research show that first appeared as constraints and not regulated and obligations  of  private  schools  in  terms  of  taxation.  Second,  the  scale  of  priority  importance of accountability between the financial manager and head  master has different values so as conflicts of interest.  Third, the implementation of transparency development from the publication  such as via the website, call center, facebook. The fourth, the Government has n ot set a standard policy  to  use of the grant allocations.